The Impact of Interpersonal Discrimination and Stress on Health and Performance for Early Career STEM Academicians - O’Brien, Katharine R.; McAbee, Samuel T.; Hebl, Michelle R.; Rodgers, John R. (Frontiers in Psychology, 2016)
The present study examines the consequences of perceived interpersonal discrimination on stress, health, and performance in a sample of 210 STEM academicians. Using a path model, we test the relation that perceived interpersonal discrimination has on stress and the relation of stress to physical health maladies and on current and future performance. In so doing, we assess the link between discrimination and decrements in performance over time. Additionally, we test supervisor social support as a moderator of the discrimination–stress relation. Findings support relations between perceived interpersonal discrimination and stress, which in turn relates to declines in physical health and performance outcomes. Moreover, supervisory support is shown to mitigate the influence of interpersonal discrimination on stress in STEM academicians.